Pengaruh Fasilitas yang Didapat dan Kompensasi Yang Seimbang Terhadap Kinerja Perawat di RSUD Gunungsitoli - Des Lastriani Hia; Juanita Juanita; Gerry Silaban (Syntax Literate, 2022)
The hospital is a health facility that provides health services to the community. The most numerous health workers in hospitals and those who often deal with patients are nurses. Nurses must have good performance so that it becomes one of the main keys in improving the quality of health services and patient satisfaction as consumers who feel the services of nurses. Nurse performance is the results achieved or achievements achieved in carrying out nursing care in hospitals. This study was conducted to analyze the effect of the variable facilities obtained and balanced compensation with the performance of nurses at the Gunungsitoli Regional General Hospital in 2020. The research method is a survey with an explanatory research approach. This research will be conducted in December 2020. The sample in this study was 139 nurses consisting of ASN nurses and BLUD nurses. From the statistical test results of the Pearson Product Moment correlation test, it is known that the variables that have a significant influence on performance are; facilities obtained (p = 0.004) while the balanced compensation variable did not have a significant effect on performance (p = 0.416). The recommendation from this research is that the Gunungsitoli Regional General Hospital always fulfills the needs and facilities for the necessary nurses and supports nurses in providing nursing care. Keywords: Facilities, Compensation, Performance